BIMBINGAN PENGAMALAN PENDIDIKAN AGAMA ISLAM OLEH GURU AGAMA TERHADAP SISWA DI SEKOLAH DASAR NEGERI 03 SUNGAI ANGEK KECAMATAN BASO KABUPATEN AGAM - RINA YUSRA; ANITA INDRIA (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2020)
One form of guidance PAI by Islamic religious teachers in the implementation of the guidance of worship is prayer time. Although the teacher has been guiding the practice of worship, students have not been able to practice their religion properly, for example, students still ignore the implementation of praying five times a day.